Analisis Faktor-Faktor Yang Mempengaruhi Underpricing Ketika Initial Public Offering (Ipo)(Studi Empiris Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2009-2013) - Ningrum, Yunita Tyas Kartika, Dr. Noer Sasongko, SE, M.Si, Akt (2015)
Underpricing is a phenomenon Initial Public Offering (IPO) which often occur in the capital market and has been proven by researchers in many countries. Underpricing occurs when the price of shares in the primary market is lower than the share price in the secondary market on the first day and the positive difference between the price of secondary market shares by the share price on the primary market at the time of the IPO is known as initial return or a positive return for investors. Initial return is a benefit shareholders because of the difference in price of shares purchased on the primary market with the selling price of the relevant shares in the secondary market. This study was conducted by researchers because the two pricing mechanism common stock of the price differences between the same shares on the primary market and the secondary market. This study aimed to analyze the factors affecting the level of underpricing. This research was conducted at the Indonesian Stock Exchange (BEI), which is the company doing an IPO in 2009 until 2013. Underpricing as measured by initial return is the dependent variable in this study. While the independent variable in this study is the underwriter reputation, auditor reputation, return on assets (ROA), and the level of leverage. The population used in this study is a company listed on the Indonesia Stock Exchange (BEI) during the years 2009-2013. Sampling method by purposive sampling according to criteria that have been determined. Total sample as many as 67 companies. Data analysis techniques used in this research is multiple linear regression analysis. Results of this study indicate that: (1) The underwriter reputation effect on underpricing, with a significance level of 0.021 <α 0.05. (2) The auditor reputation effect on underpricing, with a significance level of 0.000 <α 0.05. (3) return on assets (ROA) affect the underpricing, with a significance level of 0.015 <α 0.05. (4) the level of leverage effect on underpricing, with a significance level. Keywords: underpricing, underwriter reputation, return on assets (ROA), and leverage levels.